Community-based health financing: empirical evaluation of the socio-demographic factors determining its uptake in Awka, Anambra state, Nigeria - Felix O. Iyalomhe; Paul O. Adekola; Giuseppe T. Cirella (BMC, 2021)
Abstract Background There is an increasing global concern of financing poor people who live in low- and middle-income countries. The burden of non-communicable diseases of these people is, by in large, connected to a lack of access to effective and affordable medical care, weak financing, and delivery of health services. Policymakers have assumed, until recently, that poor people in developing countries would not pay health insurance premiums for the cost of future hospitalization. The emergence of community-based health financing (CBHF) has brought forth a renewed and empowered alternative. CBHF schemes are designed to be sustainable, varying in size, and well organized. Developing countries, such as Nigeria, have been testing and finetuning such schemes in the hope that they may 1 day reciprocate high-income countries. Methods A sample size of 372 respondents was used to assess the slums of Awka, the capital city of Anambra State, Nigeria, and empirically evaluate the socio-demographic characteristics of those who uptake CBHF using the provider Jamii Bora Trust (JBT). Cross-sectional research used a quantitative research approach with the instrumentality of structured questionnaires. Descriptive analysis was adopted to determine the socio-demographic characteristics of those who have CBHF uptake in Awka and evaluate the presence and benefits of CBHF in the city's slums. Results The results show that more youth and middle-aged persons from 18 to 50 years are more insured (i.e., 73.8% combined) than those who are over 50 years of age. Gender distribution confirm more females (i.e., 61.9%) to be health-insured than their male counterpart (i.e., 38.1%). This perhaps reflected the reproductive roles by women and the fact that women have better health-seeking behavioral attitude. Moreover, the results correlate with previous studies that confirm women are more involved in local sustainable associations in low-income settings, of this nature, in sub-Saharan Africa. Corroborating this further, married people are more insured (i.e., 73.8%) than those who are not married (i.e., 26.2%) and insured members report higher use of hospitalization care than the non-insured. Conclusion CBHF uptake favored members in the lower income quintiles who are more likely to use healthcare services covered by the JBT scheme. This confirmed that prepayment schemes and the pooling of risk could reduce financial barriers to healthcare among the urban poor. Recommendations are suggested to improve enrollment levels in the CBHF programs.